An Instruction-Level Functionality Based TricoreTM Power Estimation Model for an Automotive Microcontroller - Sachin M. N., Dr. Gayathri S., Eswar Goda (International Journal of Advanced Science and Technology, 2020)
Estimating the power consumption of any embedded applications is a key factor in optimizing automotive microcontroller power consumption. A novel approach for power estimation of automotive microcontroller is being proposed. The concept is to examine the power consumption in an automotive microcontroller from the perspective of the real software programs or instructions executed by the processor. Existing methodologies are using architectural level analysis of microcontrollers, since this technique works at more elevated abstraction levels, the estimates of the power provided by them are not extremely precise. Hence, the aim of this work is to create an instruction-level measurement based TricoreTM power estimation model that includes all the instruction set, different kind of memories, data  and also the operands which can be used to evaluate software or the instructions that are executing in terms of the power consumption in pre-silicon environment.